Association between urinary levels of 8-hydroxy-2-deoxyguanosine and F2a-isoprostane in male football players and healthy non-athlete controls with dietary inflammatory and antioxidant indices - Zare, Mahsa; Shateri, Zainab; Nouri, Mehran; Sarbakhsh, Parvin; Eftekhari, Mohammad Hasan; Pourghassem Gargari, Bahram (Frontiers in Nutrition, 2023)
Purpose The relationship between the inflammatory and antioxidant potential of an athlete's diet and their oxidative biomarkers is an important area of investigation. Therefore, this study aimed to assess the excretion of 8-hydroxy-2-deoxyguanosine (8-OHdG) and F2alpha-isoprostane (F2a-IP) in the urine of male football players and healthy non-athlete controls. This study also aimed to examine the associations among the dietary inflammatory index (DII), the dietary total antioxidant capacity (DTAC), and the dietary phytochemical index (PI) with 8-OHdG and F2a-IP. Methods In this descriptive-analytical study, 45 male football players and 45 healthy non-athletes, who were individually matched based on age and body mass index (BMI), were recruited from Shiraz City, Iran. Fasted urine samples were analyzed for 8-OHdG and F2a-IP levels. Anthropometric measurements were performed, and body composition was assessed using a body composition analyzer. A valid food frequency questionnaire (FFQ) was used to calculate DII, DTAC, and PI scores. Data analysis was conducted using a generalized estimating equation (GEE) model. Results We found that 8-OHdG (β = −6.96), F2a-IP (β = −82.58), and DII (β = −2.06) were significantly lower, while DTAC (β = 2.37) and PI (β = 0.084) were significantly higher in the football player group compared with the non-athlete group (P < 0.001 for all variables). In all participants, dietary indices were significantly associated with oxidative biomarkers. DII was positively associated with 8-OHdG (β = 2.25; P < 0.001) and F2a-IP (β = 38.34; P < 0.001). Furthermore, negative associations between DTAC (β = −1.42; P < 0.001) and PI (β = −35.37; P < 0.001) with 8-OHdG were found. Moreover, DTAC (β = −17.34; P < 0.001) and PI (β = −428.11; P = 0.003) were negatively associated with F2a-IP. Conclusion The results of this study highlighted the importance of a healthy diet in reducing oxidative stress among football athletes. The levels of urinary biomarkers for DNA and lipid oxidation were found to be lower in football players compared to non-athletes. This suggests that following an anti-inflammatory and antioxidant-rich diet may help reduce oxidative stress in these individuals.